Studi Etnoekologi Upaya Pelestarian Lingkungan Melalui Upacara Mendhak Sanggring di Desa Tlemang Lamongan - Verawati, Eka; Bazlina Wardani, Imaniah (Journal of Comprehensive Science, 2025)
This study examines the Mendhak Sanggring Ceremony in Tlemang Village, Lamongan, from an ethnoecological perspective as an effort to preserve the environment. This ceremony is an annual tradition that reflects the local wisdom of the community in maintaining the balance of nature through a series of rituals, such as cleaning the spring (Sitting Sendang), preserving the tombs of ancestors (Bersih Cungkup), and processing traditional food (Masak Sanggring). This study uses a qualitative method with an ethnographic approach, through observation, interviews, and documentation. The results of the study show that the Mendhak Sanggring Ceremony not only functions as a tribute to ancestors, but also becomes a form of culture-based environmental conservation. The community has been applying the principle of ecosystem balance for generations by maintaining clean water, protecting certain fauna, and preserving the forests around the village. These findings confirm that local knowledge has an important role in maintaining environmental sustainability, and can be a model in sustainable community-based conservation.